2013
DOI: 10.3109/10641955.2013.813535
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of apelin in placentas from severe pre-eclampsia patients

Abstract: A functional role of the apelin--APJ system is likely in early gestation, and this raises the possibility that a dysfunctional apelin--APJ system contributes to the onset of pre-eclampsia via decreased angiogenic activity in placental implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 40 publications
4
39
1
4
Order By: Relevance
“…Apelin exhibits a hypotensive effect through an endothelium and nitric oxide-dependent mechanism, with lower levels observed in patients with hypertension (35). Our data are the first to report that apelin expression in the maternal endothelium in PE is decreased and follows the same pattern of decreased expression in the placenta (18). Additionally, we observed a decrease in prostacyclin synthase expression, which suggests decreased prostacyclin production and supports previous data of decreased circulating prostacyclin levels in PE (8).…”
Section: A T 1 R E T a R E T B Rsupporting
confidence: 79%
“…Apelin exhibits a hypotensive effect through an endothelium and nitric oxide-dependent mechanism, with lower levels observed in patients with hypertension (35). Our data are the first to report that apelin expression in the maternal endothelium in PE is decreased and follows the same pattern of decreased expression in the placenta (18). Additionally, we observed a decrease in prostacyclin synthase expression, which suggests decreased prostacyclin production and supports previous data of decreased circulating prostacyclin levels in PE (8).…”
Section: A T 1 R E T a R E T B Rsupporting
confidence: 79%
“…Plasma apelin measured at delivery was reported to be lower (6), not different (29), or higher (20) in women with preeclampsia compared with women with normal pregnancy. It is known that apelin levels are influenced by endogenous enzyme inhibitors that are present in the plasma (58).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently investigated the expression of apelin in human placenta. Inzukua et al (20) reported that apelin mRNA and immunohistochemical peptide levels were lower in placentas from preeclamptic women. Our findings agree with this study and demonstrate that total apelin content in the chorionic villi is 30% lower in preeclamptic women as quantified by direct RIA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that apelin is also closely associated with normal pregnancies and pre-eclampsia. Compared with normal pregnancies, the RNA and protein level of apelin are significantly decreased in pre-eclamptic placentas (79,80). The above findings suggest that the reduced expression of apelin may be associated with preeclampsia and the apelinergic system plays an important role in preeclampsia-induced hypertensive maternal disorders.…”
Section: Apelin Inhibits Hypertension In Pre-eclampsia By Regulating mentioning
confidence: 57%